Dimensional variations of general curved composite parts - Dong, Chensong (Trans Tech Publications Inc, 2008)
With the increasing demands of energy efficiency and environment protection, composite materials have become an important alternative for traditional materials. Composite materials offer many advantages over traditional materials including: low density, high strength, high stiffness to weight ratio, excellent durability, and design flexibility. Despite all these advantages, composite materials have not been as widely used as expected because of the complexity and cost of the manufacturing process. One of the main causes is associated with poor dimensional control. General curved composite parts are often used as the structural components in the composite industry. Due to the anisotropic material nature, process-induced dimensional variations make it difficult for tighttolerance control and limit the use of composites. This research aims to develop a practical approach for the design of general curved composite parts and assembly. First, the closed-form solution for the process-induced dimensional variations, which is commonly called spring-in, was derived. For a general curved composite part, a Structural Tree Method (STM) was developed to divide the curve into a number of pieces and calculate the dimensional variations sequentially. This method can be also applied to an assembly of composite parts. The approach was validated through a case study. The method presented in this paper provides a convenient and practical tool for the dimensional and tolerance analysis in the early design stage of general curved composite parts and assembly, which is extremely useful for the realization of affordable tight tolerance composites. It also provides the foundation of Integrated Product/Process Development (IPPD) and Design for Manufacturing/Assembly (DFM/DFA) for composites.